{#289-128} : poems - Horton, Randall (University Press of Kentucky new poetry and prose series., 2020)
""Forgive state poet #289-128 / for not scribbling illusions / of trickery as if timeless hell / could be captured by stanzas / alliteration or slant rhyme," remarks the speaker, Maryland Department of Corrections prisoner {#289-128}, early in this haunting collection. Three sections-{#289-128} Property of the State, {#289-128} Poet-in-Residence (Cell 23), and {#289-128} Poet in New York-frame the myriad ways in which the narrator's body and life are socially and legally rendered by the state even as the act of poetry offers the hope of reclaiming an identity. These poems address the prison industrial complex, the carceral state, the criminal justice system, racism, violence, love, resilience, hope, and despair while exploring the idea of freedom in a cell. In the tradition of Dennis Brutus's Letters to Martha, Wole Soyinka's A Shuttle in the Crypt, and Etheridge Knight's The Essential Etheridge Knight, {#289-128} challenges the language of incarceration-especially the ways in which it reinforces stigmas and stereotypes. Though {#289-128} refuses to be defined as a felon, this collection viscerally details the dehumanizing effects of prison, which linger long after release. It also illuminates the ways in which we all are relegated to cells or boundaries, whether we want to acknowledge it or not"--